“The law” and and protests: A case study of public rhetoric in the #RUReferenceList rape culture protests at Rhodes University, South Africa - Jones, M.; Macleod, C. I.; Chiweshe, M. T. (South African Journal of Higher Education, 2025)
Where legislation is not itself the central point of dispute in higher education protests, “the law” may be used as a rhetorical strategy to bolster arguments. We use the case study of the #RUReferenceList rape culture protests at Rhodes University in 2016 to highlight the implications of “the law” as a rhetorically persuasive device. We analysed 16 public posts from “official” communication channels and 34 “unofficial” posts on Facebook following the protests. On “official” platforms, it was argued that the University’s actions aligned with the Constitution and subsequent national laws. On “unofficial” platforms, rhetors contested the University’s “narrow law and order” responses, appealing to the Constitution. Our case study illustrates how the ethos or credibility accruing to higher education institutions means that rhetorical appeals to external legal authorities, such as the Constitution, may outweigh counter–arguments made by social movements about social justice. Rapprochement could be effected through highlighting distributive and recognition injustices in the context of progressive law.